Reflexiones sobre un modelo autorial: para la historia de la fotografía en Colombia - Rueda Fajardo, Santiago (CALLE14: revista de investigación en el campo del arte, 2007)
The founding stories of the photographic medium were written in the authorial model whose creation is attributed to Beaumont Newhall. This type of historical ralatos present symptoms of wear, especially in the face of the emergence of new modes of investigation. In our country, where the history of photography is a very recent field of studies, the authorial model has barely been authorized and has a valid application, especially if it is used in a multidisciplinary research model. The purpose of this paper is to describe and propose possible new models and the benefits that it can bring, especially if it is used and supported by the iconological interpretation.